Association of elevated glycated hemoglobin and obesity with afternoon napping for more than 1 h in young and middle-aged healthy adults - Al-Abri, Mohammed A.; Al Lawati, Ibtisam; Al Zadjali, Fahad (Frontiers in Psychiatry, 2022)
Introduction Sleep has different patterns followed worldwide and can be influenced by social, cultural, and environmental factors. Daytime napping is commonly practiced in different parts of the world with controversial results of its effect on glucose metabolism. The current study aims to examine the association of afternoon napping and night sleep duration with metabolic derangements. Methods This is a cross-sectional study involving young adults and middle-aged subjects. Anthropometric measurements were taken for height and weight and hip and waist ratio. Consented subjects were asked to wear actigraphy for 1 week and run their usual daily activities. Home sleep apnea testing was performed to exclude obstructive sleep apnea. Subjects had been asked to come fasting on day seven for blood collection to test for fasting glucose, glycated hemoglobin, lipid profile, and insulin. Results A total of 405 subjects were involved to complete the study (52% male, 48% female). The mean age of participants was 32.8 ± 11.5 years. The study indicated that the duration of afternoon napping was significantly associated with abnormal glycated hemoglobin (HbA1c > 5.7%) (p = 0.01) and body mass index (p = 0.046) independent of age, gender, and nocturnal sleep duration. Nocturnal sleep duration was associated with increased insulin level (p = 0.04). Conclusion Afternoon napping is associated with an increased level of glycated hemoglobin and obesity and that may predispose to the development of type 2 diabetes mellitus.